Spinning Q-balls in Five-Dimensional Spacetime: Bintoro Anang Subagyo - Bintoro Anang Subagyo Bintoro Anang Subagyo (Lembaga Penelitian dan Pengabdian Kepada Masyarakat, LPPM-ITS, 2019)
We investigate q-balls in the d=5 dimensional Minkowski spacetime background with axially symmetric ansatz. In this case, q-balls have non-zero angular momentum for spinning problems. We construct spinning q-balls in five dimensions and solve the solutions of second order elliptic partial differential equations both using analytical and numerical approach since no closed form of the equations following by appropriate boundary conditions. This work only considers the case with equal angular momentum rather than two different angular momenta. Passing the solutions, we discuss the global charge and their properties compared to Coleman q-balls. The solutions exist in some range of frequencies. The main features of q-balls are still recovered in this construction.